An investigation on the punching shear capacity of plastered brickwall / Azhar Abdullah - Abdullah, Azhar (1996)
Proper design concept developed in many code of practice are suitable to a particular foreign experience. Bricks are local material which varies in properties from country to country. This project try to investigate the punching shear capacity of plastered brickwall.